Association Between Immunoglobulin E Levels and Kaposi Sarcoma in African Adults With Human Immunodeficiency Virus Infection - Byakwaga, Helen; Guerrero, Arturo Barbachano; Wang, Dongliang; McAllister, Shane; Naphri, Kamal; Oketta, Miriam Laker; Muzoora, Conrad; Hunt, Peter W.; Martin, Jeffrey; King, Christine A. (The Journal of Infectious Diseases, 2021)
It has been demonstrated that activated mast cells (MCs) are enriched in Kaposi sarcoma (KS) tumors and contribute to the inflammatory microenvironment. Mechanisms driving MC activation, however, are incompletely understood. We sought to understandwhether immunoglobulin E (IgE), a potent activator of MCs, was associated with KS incidence and severity. In a cross-sectional study of untreated human immunodeficiency virus (HIV)–infected adults with or without KS in Uganda, we found that patients with KS had higher plasma IgE levels than those without KS. After adjustment for age, sex, CD4+ T-cell count, and HIV RNA levels, there was a dose-response relationship between plasma IgE levels and the presence and severity of KS. Higher eosinophil counts were also associated with IgE levels, and plasma interleukin 33 concentrations were higher in individuals with KS. These findings suggest that IgE-driven atopic inflammation may contribute the pathogenesis of KS. Therapies targeting IgE-mediated MC activation thus might represent a novel approach for treatment or prevention of KS
Keywords: Immunoglobulin E (IgE); Mast cell; KSHV; IL-33; Kaposi sarcoma; HIV; Africa